Pratiques et stratégies d'apprentissage d'étudiants de 1re année de Licence et participation à un dispositif « apprendre à apprendre » : étude des déterminants et approche motivationnelle - Julien Berthaud; Lucie Corbin; Amélie Duguet; Elsa Lang Ripert; Marielle Le Mener; Sophie Morlaix
Interest in the success of first-year university students persists in public education policies. It is materialized, among other things, by the deployment of constantly renewed help and remediation devices. This work seeks to shed light on the study strategies used by the students. The challenge of this article also rest on the understanding of the determinants of these practices among first-year undergraduate students and their appropriation of a "learning to learn" module. A first aspect of the work shows a massive use of ineffective practices. Furthermore, if the results support gendered practices for the benefit of girls, they show in particular the use of effective practices more frequent among girls. The use of effective practices also turns out to be motivated, a feeling of being a good student, and having a general baccalaureate. In addition, it is interesting to note that the difficulties mentioned by the students are finally those which were the subject of the content provided in the device for learning to learn. Despite this adequacy, students take very little advantage of this opportunity, particularly those who would need it most.